Mesenchymal stem cell‐derived extracellular vesicles in treatment against renal fibrosis - Jiantao Wang; Jianxin Cui; Shengqiang Yu; Shujie Xia (Wiley, 2023)
Abstract Background Renal fibrosis (RF) is the main pathological pathway of acute kidney injury and chronic kidney disease. Its main pathological feature is extracellular matrix aggregation in the renal stroma and glomerulus. There is currently no effective treatment to delay or treat RF. Mesenchymal stem cells (MSCs) are multipotent somatic stem cells that can direct differentiation, direct cell‐cell interactions and have secretory activity. The most important secretory activity of MSCs is mediated by extracellular vesicles (EVs). At present, there is increasing evidence that EVs produced by MSCs may be used in regenerative methods of tissue repair. Aim The goal of this review is to present the latest efficacy of MSC‐EVs in the prevention, treatment and improvement of RF caused by acute and chronic kidney injury and reveals the molecular mechanism of MSCs in various models. Results and discussion MSC‐EVs show potential for RF by regulating autophagy, inhibiting apoptosis, countering oxidation, suppressing inflammation, reducing EMT and modulating angiogenesis. Conclusion MSC‐EVs show potential for treating RF. However, more studies establishing their safety, efficiency and specific mechanisms in the context of RF are still needed before further clinical application.